Basic Algebra Ability Analysis of Junior High School students with the Rasch Model Approach - Rustam, Ahmad; Iriyadi, Deni; Ekadayanti, Waode; Ahmad, Ahmad; Sasmin, Sasmin (Universitas Sembilanbelas November Kolaka, 2023)
The purpose of this study was to determine students' basic algebraic abilities based on the analysis of the items (items) and the analysis of students' abilities (person) using the Rasch modeling. The instrument used is a test instrument in the form of multiple choices about algebraic material. This test was given to 662 students of class VIII and IX at SMP Negeri 5 Kendari. Data analysis was performed by RASCH modeling using the Winstep application. The results of the person analysis stated that the overall ability of the students was greater than the difficulty level of the questions. This shows that the consistency of students' answers in solving multiple choice questions on algebraic material according to the level of difficulty is strong or good, but the quality of the items used in collecting data on students' algebraic abilities is of moderate quality.